Bioluminescence biosensing platforms for One Health: From paper sensors to thread-based analytical devices - Michelini Elisa; Gregucci Denise; Nazir Faisal; Maiorano Emanuela; Calabretta Maria Maddalena (EPJ Web of Conferences)
Bioluminescence is a fascinating phenomenon in which photons are emitted as byproduct of a chemical reaction occurring in living organisms, including bacteria, fireflies, and several marine species. Here we report the development of novel bioluminescent tools and strategies which can be used to improve the analytical performance of paper-based smartphone biosensors. In particular two new applications are reported based on paper and thread-based bioluminescent biosensors.